Reimagining Geometry through Matheor: A Classroom-Based Study on Digital Engagement and Student Motivation - Nuphanudin; Maulana, Mokhamad Nizar; Saputri, Agiska Maya; Rozany, Nasywa Rafifatur; Rahmasyani, Vergi Mutia; Ayob, Noorseha Binti (The Indonesian Institute of Science and Technology Research, 2025)
This study aims to explore the effectiveness of the Matheor application as an innovative tool in increasing students' interest in learning mathematics, particularly geometry, at the junior high school level. This study was conducted using a mixed-method approach, which combines qualitative and quantitative data collection to provide a comprehensive understanding of students' learning experiences and their engagement. Quantitative data were obtained through a structured survey using a 5-point Likert scale, while qualitative data were collected through semi-structured interviews with 15 selected students from three junior high schools in Surabaya, Indonesia. The results showed that the Matheor application significantly increased students' interest and motivation in learning to understand two-dimensional and three-dimensional geometry concepts. Most students reported increased engagement and satisfaction with mathematics learning after using the application. Qualitative data analysis revealed that Matheor's interactive and visual features helped students better understand abstract concepts. Although some students experienced challenges in the initial use of the application, they generally felt more confident and motivated to learn. The discussion of the results shows that educational technology, when well designed, can change the way students interact with difficult subject matter, such as geometry. This study concludes that Matheor has great potential to be integrated into the mathematics curriculum, supporting national education goals in strengthening STEM education. However, further research with larger and more diverse samples is needed to test the effectiveness of this application in various educational contexts.